Activating Basal Planes and S‐Terminated Edges of MoS2 toward More Efficient Hydrogen Evolution. (27th December 2016) - Huang, Xiaolei; Leng, Mei; Xiao, Wen; Li, Meng; Ding, Jun; Tan, Teck Leong; Lee, Wee Siang Vincent; Xue, Junmin
Abstract : Molybdenum disulfide (MoS2 ) has been considered as a promising alternative to platinum (Pt)‐based catalyst for hydrogen evolution reaction (HER) due to its low cost and high catalytic activity. However, stable 2H phase of MoS2 (2H‐MoS2 ) exhibits low catalytic activity in HER due to the inert basal plane and S‐edge. Thus, to exploit the basal plane and S‐edge for additional electrocatalytic activity, a facile strategy is developed to prepare P‐doped 2H‐MoS2 film on conductive substrate via low‐temperature heat treatment. Due to the inherent difficulty of P‐doping into MoS2 crystal structure, oxygen (O)‐doping is utilized to aid the P‐doping process, as supported by the first‐principles calculations. Interestingly, P‐doping could dramatically reduce Mo valence charge, which results in the functionalization of the inert MoS2 basal plane and S‐edge. In agreement with simulation results, P‐doped 2H‐MoS2 electrode exhibits enhanced catalytic performance in H2 generation with low onset potential (130 mV) and small Tafel slope of 49 mV dec −1 . The enhanced catalytic performance arises from the synergistic effect of the activated basal plane, S‐edge, and Mo‐edge sites, leading to favorable hydrogen adsorption energies. Most importantly, improved cyclic stability is achieved, which reveals chemically inert properties of P‐doped 2H‐MoS2 in acidic electrolyte. Abstract : P‐doped MoS2 is synthesized via a facile, efficient, and low‐temperature non‐metal doping method, whereby O‐doping plays a crucial role in lowering the formation energies. P‐doping can dramatically decrease hydrogen evolution reaction overpotential due to the lowering of Mo valance charge, hence promoting electron transfer from MoS2 to hydrogen ions.